Lupus high-density lipoprotein induces proinflammatory responses in macrophages by binding lectin-like oxidised low-density lipoprotein receptor 1 and failing to promote activating transcription factor 3 activity. Issue 3 (19th August 2016) - Smith, Carolyne K; Seto, Nickie L; Vivekanandan-Giri, Anuradha; Yuan, Wenmin; Playford, Martin P; Manna, Zerai; Hasni, Sarfaraz A; Kuai, Rui; Mehta, Nehal N; Schwendeman, Anna; Pennathur, Subramaniam; Kaplan, Mariana J
Abstract : Objectives: Recent evidence indicates that high-density lipoprotein (HDL) exerts vasculoprotective activities by promoting activating transcription factor 3 (ATF3), leading to downregulation of toll-like receptor (TLR)-induced inflammatory responses. Systemic lupus erythematosus (SLE) is associated with increased cardiovascular disease risk not explained by the Framingham risk score. Recent studies have indicated oxidised HDL as a possible contributor. We investigated the potential mechanisms by which lupus HDL may lose its anti-inflammatory effects and promote immune dysregulation. Methods: Control macrophages were challenged with control and SLE HDL in vitro and examined for inflammatory markers by real-time qRT-PCR, confocal microscopy, ELISA and flow cytometry. Lupus-prone mice were treated with an HDL mimetic (ETC-642) in vivo and inflammatory cytokine levels measured by real-time qRT-PCR and ELISA. Results: Compared with control HDL, SLE HDL activates NFκB, promotes inflammatory cytokine production and fails to block TLR-induced inflammation in control macrophages. This failure of lupus HDL to block inflammatory responses is due to an impaired ability to promote ATF3 synthesis and nuclear translocation. This inflammation is dependent on lectin-like oxidised low-density lipoprotein receptor 1 (LOX1R) binding and rho-associated, coiled-coil containing protein kinase 1 and 2 (ROCK1/2) kinase activity. HDL mimetic-treated lupus mice showed significant ATF3 induction and proinflammatory cytokine abrogation. Conclusions: Lupus HDL promotes proinflammatory responses through NFκB activation and decreased ATF3 synthesis and activity in an LOX1R-dependent and ROCK1/2-dependent manner. HDL mimetics should be explored as potential therapies for inflammation and SLE cardiovascular risk.